Circulating kidney injury molecule‐1 as a biomarker of renal parameters in diabetic kidney disease. Issue 2 (21st September 2019) - Gohda, Tomohito; Kamei, Nozomu; Koshida, Takeo; Kubota, Mitsunobu; Tanaka, Kanako; Yamashita, Yoshinori; Adachi, Eri; Ichikawa, Saki; Murakoshi, Maki; Ueda, Seiji; Suzuki, Yusuke
Abstract: Aims/Introduction: Urinary kidney injury molecule‐1 (KIM‐1) has been associated with proximal tubular damage in human and animal studies. Although it has been recognized as a biomarker of acute kidney injury and chronic kidney disease, its significance in the serum remains unclear. Therefore, we examined the relationship of serum and urinary KIM‐1 levels with renal parameters in patients with type 2 diabetes. Materials and Methods: Serum and urinary KIM‐1 levels, together with urinary liver‐type fatty acid‐binding protein, were measured in 602 patients with type 2 diabetes and an estimated glomerular filtration rate (eGFR) ≥30 mL/min/1.73 m 2 . These were then compared with the urinary albumin‐to‐creatinine ratio and eGFR. Results: The serum and urinary KIM‐1 levels were significantly different among the three (eGFR ≥60, 45–59, <45 mL/min/1.73 m 2 ) groups. These levels were positively associated with the albumin‐to‐creatinine ratio and negatively associated with eGFR. In a multivariate logistic model, both serum and urinary KIM‐1 were associated with an increased albumin‐to‐creatinine ratio (>30 mg/g Cr), but only the serum KIM‐1 was associated with a lower eGFR (<60 mL/min/1.73 m 2 ), after adjustment for covariates. Conclusions: Renal parameters appear to be strongly associated with serum KIM‐1, and not urinary KIM‐1, in patients with type 2 diabetes and an eGFR ≥30 mL/min/1.73 m 2 . Abstract : Both serum and urinary kidney injury molecule‐1 were associated with an increased albumin‐to‐creatinine ratio, but only serum kidney injury molecule‐1 was associated with a lower estimated glomerular filtration rate after adjustment for covariates in patients with type 2 diabetes and an estimated glomerular filtration rate ≥30 mL/min/1.73 m 2 .